Cover Picture: Edge‐hydroxylated Boron Nitride for Oxidative Dehydrogenation of Propane to Propylene (ChemCatChem 10/2017). Issue 10 (23rd May 2017) - Shi, Lei; Wang, Dongqi; Song, Wei; Shao, Dan; Zhang, Wei‐Ping; Lu, An‐Hui
Abstract : The Front Cover shows an edge‐hydroxylated boron nitride that can efficiently catalyze the oxidative dehydrogenation of propane to propylene.In their Full Paper, L. Shi et al. demonstrate that boron nitride, upon steam activation to generate B−OH groups at the edges, offers rather high selectivity toward propylene (up to 80.2 %) and a significantly minimized CO2 emission at a given propane conversion of 20.6 %. The hydrogen abstraction of B−OH groups by molecular oxygen dynamically generates the active sites, which triggered propane dehydrogenation by selectively breaking the C−H bond, but simultaneously shuts off the pathway of propylene over‐oxidation towards CO2 . More information can be found in the Full Paper by L. Shi et al. onpage 1788 in Issue 10, 2017 (DOI:10.1002/cctc.201700004 ).